what is the algebraic expression for the following word phrase: the sum of 4g and 6
10g
4g+6
4g-6
4g/6
11 answers
4g+6
What is the algebraic expression for the following word phrase: the quotient of 8 and the sum of 3 and m?
8/3+m
8/3+8m
8(3+m)
8/3-m
8/3+m
8/3+8m
8(3+m)
8/3-m
8/(3+m)
what is the algebraic expression for the following word phrase: the quotient of x and 6y?
x/6
x/6y
6xy
x-6y
x/6
x/6y
6xy
x-6y
x/(6y)
Which word phrase can you use to represent the algebraic expression 6y?
6 less than a number y
the sum of 6 and a number y
the product of 6 and a number y
the quotient of a number y and 6
6 less than a number y
the sum of 6 and a number y
the product of 6 and a number y
the quotient of a number y and 6
the product of 6 and a number y
what is the value of xy/w if x=-3, y=4, and w=-6
2
-2
1/2
-1/2
2
-2
1/2
-1/2
To find the value of xy/w, we substitute x = -3, y = 4, and w = -6 into the expression:
(-3)(4)/(-6)
= -12/-6
= 2
So, the value of xy/w is 2.
(-3)(4)/(-6)
= -12/-6
= 2
So, the value of xy/w is 2.
A gym membership costs $25 to join and $14 each month. Write and use an algebraic expression to find the cost of the gym membership for 6 months.
To find the cost of the gym membership for 6 months, we need to consider the initial joining fee of $25 and the monthly fee of $14.
Let's set up an algebraic expression:
Cost of gym membership for 6 months = 25 + (14 * 6)
Now, we can calculate the cost:
Cost of gym membership for 6 months = 25 + (14 * 6) = 25 + 84 = $109
Therefore, the cost of the gym membership for 6 months is $109.
Let's set up an algebraic expression:
Cost of gym membership for 6 months = 25 + (14 * 6)
Now, we can calculate the cost:
Cost of gym membership for 6 months = 25 + (14 * 6) = 25 + 84 = $109
Therefore, the cost of the gym membership for 6 months is $109.